Factors Affecting the Utilization of Maternal and Child Health Care Services in Tribal Dominated Population States of India. (October 2021) - Chauhan, Bal Govind; Jungari, Suresh
The present study intended to examine that factors affecting the utilization of maternal health services in the Three tribal-dominated states of India namely Madhya Pradesh, Jharkhand and Chhattisgarh. The study used National Family Health Survey (NFHS-4) data. Both bivariate and multivariate techniques have been applied for data analysis. Logistic regression techniques and concentration curve and index have been used . Findings of the study indicate that there were wider socio-economic differential exits in the utilization of MCH services (full ANC, Safe delivery and post-natal care) in all the three states under study. The regression result shows that the tribal population is less likely to utilize maternal and child health care services than other Caste groups. The economic inequality in accessing the all three components of maternal health care utilization was higher in the Jharkhand than Madhya Pradesh and Chhattisgarh. Further, economic inequality was higher in accessing the full ANC than safe delivery and post-natal care across all the states under study. From policy point of view, the government schemes to provide maternal health services to tribal communities should consider the community-level factors affecting maternal health care utilization and should extend its operations in the small villages.